LARAWUDHU : SAJIAN MRABOT DAN KAJIAN GARAP GENDER - Tofiq Hidayah; Bambang Sosodoro Rawan Jayantoro (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2023)
This research is expected to be a vokabuler of mrabot garap with specific studies of gending dynamics and popularization of Larawudhu gendhing using kendang inggah garap. Larawudhu itself is generally served using the inggah-inggahan, namely ladrang Clunthang. In this study, it will be explained about the series of gendings selected to achieve the desired gending dynamics. The concepts used include; the concept of garap by Rahayu Supanggah, the concept of mandheg by Ananto Sabdo Aji, the concept of mungguh by Bambang Sosodoro, and the concept of wiledan gender kembang tiba & ukel pancaran by Sumarsam. The method used is qualitative by means of book literature studies or related research, direct and indirect observations are also carried out to expand the author's knowledge in reviewing this research, as well as interviews with karawitan experts as input or advice for the author in conducting research. The results of this analysis offer or novelty of the work include; Larawudhu is presented using inggah kendang without changing the essence of gending Larawudhu itself, vokabuler offers mrabot with a series of gending – gending that are not similar, garap ciblon irama wiled and rangkep as an alternative garap in the form of inggah, as well as doing garap andhegan with consideration as a reinforcement of prenes elements in the garap of ciblon irama rangkep.